Road And Construction Capital Expenditure's Impact on Economic Growth of Nigeria - Oluwaseun, Oladipo A.; Saheed, Saheed, Z.; Egwaikhide, C.I.; Abraham, Alexander A.; Ikubor, Jude O. (Social Science Research, 2024)
The importance of road and construction sector as an integral part of any economy cannot be overemphasized. However, the challenges of road and construction sector are not only limited to bad and dilapidated roads, but also lack of adequate funding to provide better infrastructure, corruption, poor quality control and construction projects taking longer than planned. Therefore, this study investigates how capital investments in roads and construction affect economic growth in Nigeria. The study used the Autoregressive Distributed Lag Model (ARDL) to evaluate the annual time series data obtained from the National Bureau of Statistics (NBS) and Central Bank of Nigeria Statistical Bulletin (CBN). The analysis encompassed the years 1981 to 2020. The statistics for capital spending on roads and construction came from the NBS, whereas the data for the GDP, government revenue, inflation, and commercial bank credit to the construction sector came from the CBN Statistical Bulletin. According to the findings, government capital spending on roads and construction, commercial bank credit to the construction sector, and government revenue all contribute to Nigeria's economic growth. The outcome also demonstrates that the inflation rate impacts Nigeria's economic growth negatively yet statistically significantly. Accordingly, the report suggests that in order to promote economic growth, the government should make sure that funding for this sector is raised and well supervised. By lowering the bank rate, the government should also encourage commercial banks to extend more loans for the construction of infrastructure.